Ultrahigh-Speed Dynamics of Micrometer-Scale Inertial Cavitation from Nanoparticles - Kwan, J; Lajoinie, G; de Jong, N; Stride, E; Versluis, M; Coussios, C (American Physical Society, 2016)
Direct imaging of cavitation from solid nanoparticles has been a challenge due to the combined nanosized length and time scales involved. We report on high-speed microscopic imaging of inertial cavitation from gas trapped on nanoparticles with a tunable hemispherical depression (nanocups) at nanosecond time scales. The high-speed recordings establish that nanocups facilitate bubble growth followed by inertial collapse. Nanoparticle size, acoustic pressure amplitude, and frequency influence bubble dynamics and are compared to model predictions. Understanding these cavitation dynamics is critical for applications enhanced by acoustic cavitation.